Single-textured insole for the less affected leg in freezing of gait: A hypothesis - Etoom, Mohammad; Altaim, Thamer Ahmad; Alawneh, Anoud; Aljuhini, Yazan; Alanazi, Fahad Salam; Gaowgzeh, Riziq Allah Mustafa; Alanazi, Abdullah Owaid; Neamatallah, Ziyad; Alfawaz, Saad; Abdullahi, Auwal (Frontiers in Neurology, 2022)
Freezing of gait (FoG) is one of the most distributing and disabling gait phenomena in people with Parkinson’s disease (PD). The current therapeutic interventions show suboptimal efficacy on FoG. Lower extremity proprioception impairments especially in the most affected leg, gait initiation hesitation, and gait asymmetry are among FoG factors, and there is a need to accurately consider them in the therapeutic approaches. Accordingly, we hypothesis that using a single textured insole for the less affected leg may improve FoG by providing proprioceptive stimulation that enhances sensory processing, and reduce the gait hesitation and asymmetry. Proprioceptive sensory stimulation for the less affected limb could be more effective than for the double legs that are currently used in rehabilitation settings due to the better sensory processing in the less affected basal ganglia.